Effects of Intrathecal Caffeic Acid Phenethyl Ester (CAPE) on IL-6 and TNF-? Levels and Local Inflammatory Responses in Spinal Cord Injuries - Akgun, Bekir; Ozturk, Sait; Artas, Gokhan; Erol, Fatih Serhat (Turkish Neurosurgical Soc, 2018)
AIM: To investigate the effects of intrathecal caffeic acid phenethyl ester (CAPE) on tissue and serum interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-a) levels following spinal cord injury (SCI) as well as its effects on edema and microhemorrhage. MATERIAL and METHODS: Forty rats were divided into four groups. The sham group underwent single-level laminectomy and then received an intrathecal injection of isotonic saline. The control group received an intrathecal injection of isotonic saline following SCI induction. The methylprednisolone (MP) group received a single dose of MP intrathecally following SCI. The CAPE group received a single dose of CAPE intrathecally following SCI. IL-6 and TNF-alpha levels were determined using the enzyme-linked immunosorbent assay (ELISA) method. Spinal cord samples were evaluated histopathologically. RESULTS: The decrease in IL-6 levels in the CAPE group was significantly higher than that in the sham and control groups. However, this decrease was not as significant as that in the MP group. No significant decrease was identified in TNF-alpha levels. A significant decrease was observed in spinal cord edema and microhemorrhage in the CAPE group. A decrease in edema was observed in the MP group, but no effect was observed on microhemorrhage. CONCLUSION: Intrathecal CAPE administration following SCI decreases tissue and serum IL-6 levels as well as decreases spinal cord edema and microhemorrhage.
Keywords: Caffeic acid phenethyl ester; Histopathology; IL-6; Spinal cord injury; TNF-alpha